Embouche intensive des zebus de l'Adamoua. 1. Comparaison de differents systems d'alimentation (1970) - Lhoste, Philippe; Dumas, R. (1972)
Compares influence of various feeding systems on meat production from Brahman x Fulani crossbreeds and indigenous breeds of zebu cattle at the Wakwa research station, Cameroon. The response to intensive fattening was better for the crossbred steers (Brahman x Fulani) than for the local breed (Fulani). The Adamawa Zebu cattle adopted perfectly to every feeding system. The carcasses obtained were of improved quality and the beef production cycle was shortened. Details on economic aspects of fattening, feed intake, weight gains and feed conversion efficiency included.